2016
DOI: 10.1155/2016/3521453
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A2 Coordinates STAT3 to Regulate the Invasion and Migration of Colorectal Cancer CellsIn Vitro

Abstract: The present study aimed to reveal the expression of STAT3 and Anxa 2 in CRC specimens and to investigate the effects of STAT3 and Anxa 2 signaling on the proliferation, invasion, and migration in CRC Caco-2 cells. Results demonstrated that both Anxa 2 and STAT3 were highly expressed in CRC specimens in both mRNA and protein levels, with or without phosphorylation (Tyrosine 23 in Anxa 2 and Tyrosine 705 in STAT3). And the upregulated Anxa 2 promoted the phosphorylation of STAT3 (Tyrosine 705) in CRC Caco-2 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
(43 reference statements)
1
14
0
Order By: Relevance
“…Furthermore, ANXA2 depletion significantly reduced cell invasion and metastatic potential of breast cancer model in vivo. Similar findings of EGF enhanced ANXA2 expression and EMT promotion were observed in cervical cancer, pancreatic cancer and colon cancer cell lines (19,27,28).…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, ANXA2 depletion significantly reduced cell invasion and metastatic potential of breast cancer model in vivo. Similar findings of EGF enhanced ANXA2 expression and EMT promotion were observed in cervical cancer, pancreatic cancer and colon cancer cell lines (19,27,28).…”
Section: Discussionsupporting
confidence: 79%
“…We have reported that pY23-Anxa2 binds to and enhances STAT3 activation and promotes invasion and metastasis of breast cancer cells [56]. Consistently, Anxa2 associates with STAT3 and confers the aggressive behavior in colorectal cancer [46,66]. Interestingly, Rack1 is also involved in the activation of STAT3 in several cancer cells [36,67].…”
Section: Discussionmentioning
confidence: 73%
“…Bcl2 and Bcl-xL expression can be regulated by STAT3, an important factor that relays signals from cytokines and growth factors to regulate gene expression in biological processes, including apoptosis induced by the JAK/STAT pathway (42,43). The relationship among GroEL, annexin A2, cell apoptosis, and the JAK/STAT pathway remains unknown and requires further studies.…”
Section: Discussionmentioning
confidence: 99%